Pension funds, capital market development, and macroeconomic variables: Evidence from Jordan. Issue 2 (20th July 2020) - Daradkah, Demeh; Al‐Hamdoun, Nadia
Abstract : This study investigates the dynamic relationship between pension funds and development of capital market in Jordan over the period 1980–2017. Autoregressive distributed lag (ARDL) approaches for co‐integration (bounds test) are employed to achieve the objectives of the study. Using annual data, the results indicate no statistically significant relationship between pension funds and development of capital market on the short run. However, the co‐integration tests show a statistically significant long‐run equilibrium relationship between pension funds and development of capital market regardless of whether capital market development was measured by market depth or market liquidity. Moreover, the co‐integration tests show a statistically significant long‐run equilibrium relationship between economic growth, and interest rate and development of capital market regardless of whether capital market development was measured by market depth or market liquidity. These findings have important implications for academics, investment managers, and policy makers in Jordan.